FROM EFFICIENT MARKET HYPOTHESIS TO BEHAVIOURAL FINANCE: CAN BEHAVIOURAL FINANCE BE THE NEW DOMINANT MODEL FOR INVESTING? - George BOROVAS; Androniki KATARACHIA; Anastasios KONSTANTINIDIS; Maria Eleni VOUTSA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The present paper reviews two fundamental investing paradigms, which have had a substantial impact on the manner investors tend to develop their own strategies. specifically, the study elaborates on efficient market hypothesis (emh), which, despite remaining most prominent and popular until the 1990s, is considered rather controversial and often disputed, and the theory of behavioural finance, which has increasingly been implemented in financial institutions. based on an extensive survey of behavioural finance and emh literature, the study demonstrates, despite any assertions, the inherent irrationality of the theory of efficient market, and discusses the potential reasons for its recent decline, arguing in favor of its replacement or co-existence with behavioural finance. in addition, the study highlights that the theory of behavioural finance, which endorses human behavioral and psychological attitudes, should become the theoretical framework for successful and profitable investing.